Creating A Safer Environment In U.S. Coal Mines - The Bureau Of Mines Methane Control Program, 1964-79 - Introduction - Milford L. Skow (The National Institute for Occupational Safety and Health (NIOSH), 1980)
This report summarizes the principal activities and results of 15 years of research by the Bureau of Mines, U.S. Department of the Interior, on methane control in coal mines. This research has investigated fundamental factors regarding the occurrence and movement of methane in coal beds, removal of methane prior to mining, and control of methane during mining. The report includes a bibliography listing the more than 150 publications resulting from the Bureau's methane control program as well as numerous other references, a section on methane recovery and use, a look at the upcoming Bureau of Mines research program, and a brief review of methane drainage practices in other coal-producing countries.